The effect of game-based learning variations on elementary school students’ straddle jump gymnastics skills - Fadhilah Nurwahid; Rizal Ahmad Fauzi; Adang Sudrazat (Physical Education and Sports: Studies and Research, 2026)
Background: Physical education in primary schools is essential for the development of students' motor skills, including gymnastic abilities such as the straddle leap. In fact, numerous students continue to struggle to execute these movements accurately because of repetitive teaching approaches that fail to engage them actively. Consequently, a more stimulating and diverse educational methodology, including game-based activities, is required. Objectives: This study examines the impact of fluctuations in game-based learning on the enhancement of straddle jump gymnastics skills among primary school students. Methods: This research employed a quantitative methodology using a pre-experimental framework, namely the One-Group Pretest–Posttest Design. The study population comprised all 40 fourth-grade students at Citungku Elementary School, who were sampled using a total sampling technique. Data were gathered via a practical examination of straddle jump movement proficiency, adhering to the Australian Gymnastic Federation's evaluation criteria, which encompass four components: the initiation, propulsion, suspended posture, and landing. The intervention lasted four weeks and included eight sessions featuring activities such as frog leaps, mirror jumps, rope jumping, and hopscotch, all aimed at training the elements of the straddle jump. The Shapiro-Wilk normality test and paired-samples t-test were conducted in SPSS version 27 for data analysis. Results: The study found an improvement in students' capabilities following the implementation of game-based learning modifications. The mean pretest score of 58.00 rose to 74.76 in the posttest. The paired-samples t-test yielded a t value of -9.894 and a p-value of 0.001 (< 0.05), indicating a significant difference between pre- and post-treatment outcomes. This demonstrates that the executed game activities facilitated improvements in students' motor coordination, push-off strength, body control during floating, and landing methods during the straddle jump movement. Conclusions: Variations of game-based learning, including frog jumping, mirror jumping, rope jumping, and hopscotch, have demonstrated efficacy in enhancing straddle jumping gymnastics skills among elementary school students while fostering a more dynamic and pleasurable physical learning experience.